ANALISIS KESESUAIAN KEBIJAKAN PEMERINTAH MENURUT SISI FINANSIAL, SUMBER DAYA MANUSIA, FARMASI DAN ALAT KESEHATAN DALAM MENANGGAPI MASALAH WISATA MEDIS, BERCERMIN PADA PROYEK KAWASAN EKONOMI KHUSUS SANUR - Tri Yuyun Apriliandika Simak; Agus Hadian Rahim; Kahar Mulyani (Media Bina Ilmiah, 2025)
Background : Large number of outbound medical tourism resulted in the loss of the country's foreign exchange. The reasons for service standards, advanced facilities and technology, low and transparent costs, and ease of access are challenges. The government through Permenkes 1 of 2023 supports health business activities in the Sanur SEZ. The research aims to determine the suitability of government policies and medical tourism problems. The methodology of qualitative approach with document study focuses on the analysis of policy documents, white papers, and relevant literature. Secondary research data is limited to inclusion and exclusion criteria, while primary data is with in-depth interviews with medical tourism policy implementers. Analysis of policy conformity with the Dunn Model framework (problem identification, forecasting, evaluation of impacts). The result obtained from the financial side of one of the problems of medical tourism is that Indonesia's high health costs (especially for ASEAN countries. Government policies provide tax relaxation with the potential to reduce costs by up to 30%. On the human resource side, the limited number of specialists in Indonesia, the queue for consultation, and the lack of patient-centered care are complaints. The relaxation of the ease of the process of entering foreign graduate health workers provides flexibility for hospitals to determine services by simplifying recruitment. In terms of support, Malaysia and Singapore offer high-quality and complete health services that do not exist in Indonesia. Relaxation of drugs and medical devices that do not have a distribution permit supports the acceleration of licensing for immediate use. From this, it is concluded that the Sanur SEZ has a great opportunity to become a competitive medical tourism center at the regional and international levels if these challenges can be overcome effectively. Hospitals should develop a strong strategy by forming a strong work team and medical tourism network.